Effect of Low pH on the Growth, Physiological Characteristics and Nutrient Absorption of Sago Palm in a Hydroponic System - Ornprapa Anugoolprasert; Shina Kinoshita; Hitoshi Naito; Masafumi Shimizu; Hiroshi Ehara (Plant Production Science, 2012)
The dry matter production, photosynthetic characteristics and nutrient concentrations in the plant tissues of sago palmseedlings cultured for 4.5 months in a hydroponic system at pH 5.7, 4.5, and 3.6 were examined. Plant growth in weekly increment of length, leaf emergence, leaf senescence, and total leaflet area was similar at all pHs. There was no significanteffect of pH on the dry matter weight, although it tended to be lighter at pH 3.6 than at pH 5.7. Similarly, the photosynthetic rate and its related parameter were not significantly affected by the pH. However, the photosynthetic rate at pH 3.6tended to be lower than that at pH 5.7, which was attributed to a decrease in the stomatal conductance. The effect of the low pH on the nutrient concentration in plant tissues was not distinct. We concluded that sago palm seedlings could maintain leaf morphogenesis and nutrient uptake in growth media at a pH ranging from 5.7 to 3.6 for 4.5 months, which led to a high growth rate and maintenance of dry matter production even at pH 3.6.